A spatial analysis of non-performance financing determinants in Islamic banks in Indonesia - Eko Suprayitno; Rizky Mubarocha Hardiani (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – This study aims to analyze the non-performance financing determinant of Islamic Banking (IB) in Indonesia through spatial analysis. These determinants consist of macroeconomic and microeconomic variablesMethodology – Samples in this research were selected using the purposive sampling technique with the criteria of Islamic banks registered in the Financial Services Authority (OJK) that released quarterly data reports and financial reports during 2015-2020. There are 7 Islamic banks that met the criteria.Findings – Results showed that the ROA, Inflation, GDP, and BI Rate simultaneously affected the NPF level, while FDR and CAR do not affect the NPF level of Islamic commercial banks. Meanwhile, partially FDR, BOPO, CAR, ROA, Inflation, GDP, and BI Rate affect the NPF level. In addition, the spatial analysis showed that based on the global distribution, there is a significant spatial effect through the geographical location between one bank and other.Originality – This research provides empirical data related to the determinants of non-performing financing, using the spatial analysis approach. Moreover, this research also uses the most updated data, Islamic and conventional banks during 2015-2020Research limitations – Related to the samples of Islamic banks, this research only investigates those registered in OJK, not all Islamic banks in Indonesia.